Increasing Farmers' Income in the Agricultural Sector in Central Java - Hamzah, Imam Royani (Sinergi International Journal of Economics, 2024)
In the agricultural sector of Central Java, this study examines the relationship between supply chain effectiveness, government policies, infrastructure development, and farmers' income. This study investigates the current status of infrastructure accessibility, government regulations, supply chain dynamics, and income sources through quantitative analyses involving 250 farmers. To verify and examine the correlation between the variables, structural equation modelling with partial least squares, or SEM-PLS, was used. Variations in the level of supply chain efficiency, farmers' attitudes towards government policies, infrastructure quality, and income distribution are shown by descriptive statistics. All proposed hypotheses were supported by the structural model, and the measurement model showed excellent levels of validity and reliability. The results of this study highlight the importance of infrastructure, sensible public policies, and efficient supply chains in increasing farmers' income. There is a discussion of practical consequences and suggestions for stakeholders and policymakers, with a focus on the need for focused action to improve the socio-economic conditions of farmers in Central Java. Although the statistical relationship between these variables is strong, farmers and the government are highly interdependent, so the real implications for the government to improve farmers in Central Java include regulation and distribution similar to other big cities.